Tungsten trioxide nanocomposite for conventional soliton and noise-like pulse generation in anomalous dispersion laser cavity - Mansor, Maisarah; Zainol Abidin, Nadiah Husseini; Mohd Yusoff, Norita; Lau, Kuen Yao; Chyi, Josephine Liew Ying; Janyani, Vijay; Garg, Amit Kumar; Alresheedi, Mohammed Thamer; Mahdi, Mohd Adzir (De Gruyter, 2023)
This work demonstrates the employment of tungsten trioxide/polydimethylsiloxane nanocomposite saturable absorber (WO3/PDMS-SA) in realizing mode-locked conventional soliton (CS) and noise-like pulse (NLP) laser generation in net anomalous dispersion. The switching formation from CS regime of 970.0‰fs pulse duration to NLP regime of 182.0‰fs coherent spike with 65.3‰ps pedestal was achieved by varying its pump power. The pulse laser exhibited good stability of 50.76 and 49.82‰dB signal-to-noise ratio at 9.09‰MHz fundamental repetition rate and trivial variation during stability test for CS and NLP regime, respectively. This work expresses the feasibility of WO3/PDMS-SA in attaining various types of mode-locked pulse phenomena using a fixed cavity configuration conceivably beneficial for compact dual-purpose laser systems.